The value of "a" is 4
<em><u>Solution:</u></em>
<em><u>Given expression is:</u></em>
![a - 2 = -1 + 2a - 4-1](https://tex.z-dn.net/?f=a%20-%202%20%20%3D%20-1%20%2B%202a%20-%204-1)
The above expression involves variables and constants
A variable is a symbol that represents an unknown number
Here the variable is "a"
Constants are fixed numbers like 1, 2 etc
<em><u>From given expression:</u></em>
![a - 2 = -1 + 2a - 4-1](https://tex.z-dn.net/?f=a%20-%202%20%20%3D%20-1%20%2B%202a%20-%204-1)
Move the varibale "2a" from right side to left side of equation
When, 2a is moved from R.H.S to L.H.S, it becomes -2a
![a -2a - 2 = -1 -4-1](https://tex.z-dn.net/?f=a%20-2a%20-%202%20%3D%20-1%20-4-1)
Now move the constant -2 from left side to right side of equation
Similarly, when -2 is moved from L.H.S to R.H.S, it becomes +2
![a-2a = -1-4-1+2](https://tex.z-dn.net/?f=a-2a%20%3D%20-1-4-1%2B2)
Now add the variables on left side of equation
![-a = -1-4-1+2](https://tex.z-dn.net/?f=-a%20%3D%20-1-4-1%2B2)
Now add the constants on right side of equation
![-a = -6+2\\\\-a = -4](https://tex.z-dn.net/?f=-a%20%3D%20-6%2B2%5C%5C%5C%5C-a%20%3D%20-4)
Cancel the negative sign on both sides of equation
![a=4](https://tex.z-dn.net/?f=a%3D4)
Thus the value of "a" is 4